A study on Malaysia traditional games ‘Konda-Kondi’ as interactive illustrations book for children readers / Nur Afiffa Zulkiflli - Zulkiflli, Nur Afiffa (2019)
In this generation is a very rare chance to see children play any of our traditional games and this is the result of abandonment and lack exposure by society. This research aims to study the creative process in creating interactive illustrations book. Traditional games are part of cultural heritages that precious to our community, that should be preserve. Having realized the importance of preserving our traditional games, this paper aims to study Malaysian traditional games ‘Konda–Kondi’ as an interactive illustrations book for children. The research will conduct and analyze using a mixed method. The findings of this study are the interactive illustrations that can help in creating a book for children and to acknowledge the young generation about the Malaysia traditional game. The paper discusses how this research can potentially give a new perspective for the children in educating them about our tradition and culture. Our traditional games are part of our cultures that have been an inheritance from the previous generations. It is something that should be embraced instead of being forgotten.